2007
DOI: 10.1044/1058-0360(2007/019)
|View full text |Cite
|
Sign up to set email alerts
|

Tongue Measures in Individuals With Normal and Impaired Swallowing

Abstract: We were able to extend the normative database on tongue function and document reduced tongue strength in a group of individuals with dysphagia. The findings provide evidence that in this group, tongue weakness coincided with signs of dysphagia, adding justification for tongue-strengthening protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
170
4
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(196 citation statements)
references
References 18 publications
12
170
4
10
Order By: Relevance
“…After that, many studies proposed to measure the pressure made by the tongue on the oral cavity (7) during functions such as speech (8) , swallowing, (5) and chewing (9) ; at rest (10) ; and during the maximum isometric contraction for comparing with different portions of the tongue (anterior and dorsum) among young adults (11) . The pressure of the tongue has also been studied in relation to gender (11)(12)(13)(14) and age (5,(13)(14)(15) in individuals diagnosed with obstructive sleep apnea (16) , neurological conditions (17) , and disorders in the head and neck area (18) . Besides, it is possible to find studies related to the exercises of the tongue (17) ; pressure of the lip and tongue regarding the type of bad occlusion (19) ; the comparison between the maximum isometric pressure of the tongue of individuals with dentofacial deformity and those with adequate occlusal relationship (20) ; and the comparison of pressure and resistance of the tongue among speakers of Brazilian Portuguese, and English, which obtained a lower resistance of the tongue for the latter (13) .…”
Section: Introductionmentioning
confidence: 99%
“…After that, many studies proposed to measure the pressure made by the tongue on the oral cavity (7) during functions such as speech (8) , swallowing, (5) and chewing (9) ; at rest (10) ; and during the maximum isometric contraction for comparing with different portions of the tongue (anterior and dorsum) among young adults (11) . The pressure of the tongue has also been studied in relation to gender (11)(12)(13)(14) and age (5,(13)(14)(15) in individuals diagnosed with obstructive sleep apnea (16) , neurological conditions (17) , and disorders in the head and neck area (18) . Besides, it is possible to find studies related to the exercises of the tongue (17) ; pressure of the lip and tongue regarding the type of bad occlusion (19) ; the comparison between the maximum isometric pressure of the tongue of individuals with dentofacial deformity and those with adequate occlusal relationship (20) ; and the comparison of pressure and resistance of the tongue among speakers of Brazilian Portuguese, and English, which obtained a lower resistance of the tongue for the latter (13) .…”
Section: Introductionmentioning
confidence: 99%
“…However, the strength reduction only occurs after age 60 (12)(13)(14) justifying the non stratification of the sample by age.…”
Section: Methodsmentioning
confidence: 99%
“…Tongue force is related, in most studies, to the age and gender of individuals. Studies have found that the tongue force decreases with the increase in age from 60 years on (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research shows that dysphagic individuals may have weakness in the musculature of the tongue (2,3) and that the strength training through isometric exercises improves performance in the swallowing (4,5) . The suprahyoid muscles also participate in the swallowing.…”
Section: Introductionmentioning
confidence: 99%